(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article deals with word-formative ways of the diminutive expression in folkloric texts, functioning of units with stylistic marking with diminutive suffixes in Ukrainian folk songs is under analysis. The functioning of the objective diminutive subcategory together with lexical and semantical differentiation of nouns with objective diminutive meaning are ascertained. The author draws conclusions about Ukrainian folk songs: there is a great deal of noun’s diminutions that denote animated creations, natural objects and facts, abstract notions that have connections with spiritual people’s life; diminutive suffixes of adjectives, adverbs and verbs can express subjective assessment where the sema of the real diminution is leveled almost or totally. Features of the functioning these diminutions without equivalents (that are derived from basises with negative semantics) in Ukrainian folk songs are researched. The most popular methods for gain the derogatory assessment is the contrast of diminutive suffix’ semantics and initial basis, the comparison or the contradistinction of lexemes with diminutive and caressing suffixes or without last ones. The researcher must take a method of context analysis for the right interpretation of the morpheme’s function with diminutive meaning. The presence of this phenomenon in Ukrainian folkloric texts is determined by psychological peculiarities of Ukrainians. The recess in the national history, the comprehension of folk traditions, ethical and aesthetic norms, the spiritual experience of the nation where aesthetic ideals are fixed, and these ideals originate from folk ideas, the historical ethnos’ existence and natural actuals, these are very advisable for understanding the process of national self-knowledge. The folklore fixes ideas (that have national determination) about the universe and the human existence, so this research will facilitate for detection of Ukrainians’ value orientations.